Latrophilin 3 variants are associated with substance abuse disorder comorbid with ADHD - Martínez, Ariel F.; Arcos Burgos, Mauricio (Iatreia, 2010)
Latrophilins comprise a new class of orphan G protein- coupled receptors that has been extensively studied involving regulated neurotransmitter exocytosis. Latrophilins are specific receptors for alpha-latrotoxin, a neurotoxin present in the black widow spider venom. A recent study by our group found l trophilin 3 (LPHN3), the most brain-specific latrophilin in mammals, to be associated with an increased susceptibility to developing attention deficit/hyperactivity disorder (ADHD), the most prevalent psychiatric condition in children and adolescents, in several populations. Sin ce ADHD is usually comorbid with other behavioral conditions, we further interrogated five LPHN3 markers for comorbid nicotine and alcohol abuse, conduct disorder and oppositional defiant disorder in a U.S. sample from Kentucky and a sample from Colombia. Interestingly, two of the markers, rs7659636 and rs4860437, were associated with substance use disorder (SUD) in both samples. These results, together with the previous findings implicating LPHN3 in the etiology of ADHD, strongly advocates for an important role of LPHN3 in psychiatric conditions and opens a new window towards the research and development of psychiatric drugs targeting this receptor family.